CHICA: A Chinese Calligraphy Mobile Learning Application for Beginners - Din, Suhaili; William Foo Boon Keat (Journal of Computing Technologies and Creative Content, 2021)
CHICA is a Chinese mobile learning application for beginners. Most of us know that Chinese language is hard to learn especially the writing. Most beginners cannot differentiate the tones of Chinese characters. There are some Chinese characters that sound the same however it has different tones andmeanings. The writing of Chinese characters is difficult for beginners too since they need to memorize characters and the stroke orders. Particle of Chinese language is different with Bahasa Malaysia. Chinese language often uses ’ma’ (chinese character) at the end of sentences while Bahasa Malaysia has many particles. This application was developed to assist beginners in learning basic Chinese with the main focus of Chinese handwritten lettering or calligraphy. CHICA consists of three categories: hanyun pinyin (vocal, consonant and tone), learning basic strokes and practice writing. This application was developed using Adobe Animate with Actionscript 3.0. The evaluation is carried out among UniKL MIIT students in Mandarin 1 class. Results show that the application helps students in understanding the basic Chinese and help them in writing practice.